-270
on expanding
= -36+9{6-32}
= -36+9{-26}
= -36-234
= -270
2007-01-09 03:38:29
·
answer #1
·
answered by Abu F 2
·
2⤊
0⤋
Solve according to order of operations ... PEMDAS >>>
( ), exponents, multiplication, division, addition and subtraction
- 4(9) + 9[6 - 8(2)(2)]
- 36 + 9[6 - 8(4)]
- 36 + 9[6 - 32]
- 36 + 9[- 26]
- 36 - 234
- 270
2007-01-09 14:16:40
·
answer #2
·
answered by ♪♥Annie♥♪ 6
·
1⤊
0⤋
You want to use PEMDAS (Parentheses, Exponents, Multiplication, Division, Addition, and Subtraction) in this problem:
You have have to work out the problem starting in the parentheses or brackets:
[6-8(2)^2]
[6-8(4)]
[6-32]
[-26]
-4(9)+9[-26]
Now, you do the multiplication:
-36+-234
The final step is to add:
-36+-234=-270
2007-01-09 12:54:30
·
answer #3
·
answered by Anonymous
·
1⤊
0⤋
this cannot be solve except if [ and } are the same. assuming they are the same then
= -4(9)+9[ 6-8(2)2 }
first remove the inner bracket
= -4(9)+9[6-16*2 }
then multiply 16*2=32
= -4(9)+9 [ 6-32 }
opening all the brackets
= -36+54-288=-270
= -270
2007-01-09 11:54:52
·
answer #4
·
answered by yason 2
·
2⤊
0⤋
-4(9)+9[6-8(2)2]
the order of operation requires you to solve the inner most set of brackets 1st operating from left to right.
step1.
-4(9)+9 [ 6 -(16)2 ]
step2.
-4(9)+9[6-32]
step 3.
-4(9)+54-288
step 4.
-36 + ( -234)
-270
2007-01-09 12:00:11
·
answer #5
·
answered by Anonymous
·
2⤊
0⤋
-4(9)+9[6-8(2)2]
-36 + 9[6-32]
-36 + 9[-26]
-36 - 234 = -270
Merci~
2007-01-09 11:49:37
·
answer #6
·
answered by Miss LaStrange 5
·
2⤊
0⤋
=-36+9[6-32]
=-36+9*-26
=-36-234
=-270
Good luck
2007-01-09 12:20:47
·
answer #7
·
answered by Anonymous
·
2⤊
0⤋
-4(9)+9[6-8(2)2}
-36+9[6-32]
-36+9[-26]
-36+-234
-270
2007-01-09 12:33:12
·
answer #8
·
answered by Saphira 3
·
2⤊
0⤋
=-36+9[6-32]
=-36+9*-26
=-36-234
=-270
2007-01-09 11:44:31
·
answer #9
·
answered by openpsychy 6
·
2⤊
0⤋
=-36+9[6-16(2)]
=-36+9(-26)
=-36-234
=-270
2007-01-09 11:43:31
·
answer #10
·
answered by Maths Rocks 4
·
2⤊
0⤋